Legitimizing a Diversity Policy in a Challenging Environment: A Case Study of a French Business School - Marais, Magalie; Joly, Cédrine; Meyer, Maryline; Jaeck, Mélanie; Kessari, Myriam; Andiappan, Meena; Dufour, Lucas (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2020)
This paper explores how a diversity policy is legitimized along moral, pragmatic and cognitive dimensions in a challenging environment (conflicting demands with regard to diversity). In this case study-based paper, we use evidence gathered from 92 interviews with members of key stakeholder groups, observation, and secondary data sources in a French business school. We find that perceptions about the legitimacy of a diversity policy may be ambivalent when legitimacy is evaluated along several dimensions. We conclude that legitimizing a diversity policy requires step-by-step management, with the organization selecting and combining various legitimization strategies over time.